Generation of Thirty-Year-Olds in Contemporary Russian Art: Characteristics of Curatorial Practice and Art Criticism - Karlova, Anastasia I. (Actual Problems of Theory and History of Art, 2022)
The research was initiated by the preparation of the exhibition “Generation of Thirty-Year-Olds in Contemporary Russian Art” in the Russian Museum (St. Petersburg, 2021). The purpose was to identify those features that characterize exhibition projects and art critics, related to the representation and analysis of the oeuvre of Russian artists of the millennial generation. The study was based on the examination of the curatorial projects and critical texts of the period from 2010 to 2020. Deep changes in culture, caused by a significant increase of the Internet influence on the society, were considered as the most important factor in the development of the art process of the period. The following features of curatorial practice were revealed: Internet culture was viewed from a critical standpoint in most projects of the decade; the most relevant forms of the exhibition were site-specific events and projects with the qualities of immersiveness; the most important component of exhibition was performance. The key trends of art criticism include: the transition from a vertical model to a horizontal one due to the growing influence of Internet publications (self-organized platforms, social networks); crucial changes in the format of the critical text (mixing genres, including multimedia objects in the text as a result of the medial turn in linguistics); the key role of the author and the emphasis on personality as the basis of a critical text.